2020
DOI: 10.3988/jcn.2020.16.4.562
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic Rims in Multiple Sclerosis and Neuromyelitis Optica Spectrum Disorder: A Quantitative Susceptibility Mapping Study with 3-T MRI

Abstract: Background and Purpose Iron retained by activated microglia and macrophages in multiple sclerosis (MS) lesions may serve as a marker of innate immune system activation. Among several magnetic resonance imaging (MRI) methods, there has been recent interest in using quantitative susceptibility mapping (QSM) as a potential tool for assessing iron levels in the human brain. This study examined QSM findings in MS and neuromyelitis optica spectrum disorder (NMOSD) lesions obtained with 3-T MRI to assess imaging char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…We emailed 14 study investigators to request additional study data or to seek clarification about study methodology, and 7 kindly replied. Not captured by our search were 5 studies that post-dated our literature search [ 20 , 29 32 ]. These were subsequently included in our sensitivity analyses.…”
Section: Resultsmentioning
confidence: 99%
“…We emailed 14 study investigators to request additional study data or to seek clarification about study methodology, and 7 kindly replied. Not captured by our search were 5 studies that post-dated our literature search [ 20 , 29 32 ]. These were subsequently included in our sensitivity analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have looked at the use of 7T MR imaging in NMOSD. These studies have shown that the rim-like and nodular pattern of paramagnetic phase changes, suggestive of iron deposition which are seen in some MS brain lesions, are not seen in NMOSD [140][141][142]. No difference in T1 relaxation time between NMOSD and healthy controls has been observed [143].…”
Section: High-field Mrimentioning
confidence: 90%
“…The T 2 and T2 maps derived from 2in1‐RARE‐EPI offer the capacity for the calculation of R2 maps, which is conceptually appealing for probing the spatial distribution of magnetic susceptibility effects 99,100 . This could be beneficial for the assessment of chronic active MS lesions that are characterized by a rim of iron‐enriched activated microglia and macrophages, probing iron levels in the deep gray matter, and for identifying regions of demyelination and iron accumulation during the formation of MS lesions 101 …”
Section: Discussionmentioning
confidence: 99%
“…99,100 This could be beneficial for the assessment of chronic active MS lesions that are characterized by a rim of iron-enriched activated microglia and macrophages, probing iron levels in the deep gray matter, and for identifying regions of demyelination and iron accumulation during the formation of MS lesions. 101 The potential of the proposed 2in1-RARE-EPI hybrid is not limited to MS lesions or even brain imaging. 2in1-RARE-EPI offers the capacity for simultaneous T 2 and T * 2 mapping in applications dealing with bulk or physiological motion, such as cardiac imaging including myocardial T 2 and T * 2 mapping, [102][103][104] as well as multi-parametric MRI of the eye, kidney, abdomen, and liver.…”
Section: And T *mentioning
confidence: 99%